Hepatic presentation of Wilson's Disease in children (International Journal of Hepatology, 2010)
Wilson's Disease is a rare autosomal recessive genetic disorder of copper metabolism which is characterized by hepatic and neurological disease. The disease affects between one in 30000 and one in 100000 individuals and was first described as a syndrome by Kinnier Wilson in 1912. In affected individuals, there is accumulation of excess copper in the liver caused by reduced excretion of copper in bile. The great danger is that Wilson’s disease is progressive, can remain undiagnosed and is to be fatal if untreated.International Journal of Hepatology Vol.1(3) 2010 pp.25-30